Diagnostic Methods of Helicobacter pylori Infection for Epidemiological Studies: Critical Importance of Indirect Test Validation - Miftahussurur, Muhammad (Biomed Res Int, 2016)
Among the methods developed to detect H. pylori infection, determining the gold standard remains debatable, especially for epidemiological studies. Due to the decreasing sensitivity of direct diagnostic tests (histopathology and/or immunohistochemistry [IHC], rapid urease test [RUT], and culture), several indirect tests, including antibody-based tests (serology and urine test), urea breath test (UBT), and stool antigen test (SAT) have been developed to diagnose H. pylori infection. Among the indirect tests, UBT and SAT became the best methods to determine active infection. While antibody-based tests, especially serology, are widely available and relatively sensitive, their specificity is low. Guidelines indicated that no single test can be considered as the gold standard for the diagnosis of H. pylori infection and that one should consider the method's advantages and disadvantages. Based on four epidemiological studies, culture and RUT present a sensitivity of 74.2–90.8% and 83.3–86.9% and a specificity of 97.7–98.8% and 95.1–97.2%, respectively, when using IHC as a gold standard. The sensitivity of serology is quite high, but that of the urine test was lower compared with that of the other methods. Thus, indirect test validation is important although some commercial kits propose universal cut-off values.